Satyrichthys kikingeri Pogoreutz, Vitecek & Ahnelt, 2013, a junior synonym of Satyrichthys laticeps (Schlegel, 1852) (Actinopterygii: Teleostei: Peristediidae) - Kawai, Toshio (Zootaxa, 2014)
Satyrichthys kikingeri Pogoreutz, Vitecek & Ahnelt, 2013 was described as a new species based on a single dried specimen from the Maldives, Indian Ocean. Although this species was considered to differ from the most similar species of the genus, S. laticeps (Schlegel, 1852), by numbers of barbels and anal fin rays, and several morphometric characters, it is clear that both species are inseparable as these characters were misinterpreted in the holotype in the original description of S. kikingeri. Therefore, S. kikingeri is a junior synonym of S. laticeps.